(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
High-selective method for asymmetric synthesis of (S)-β-(3-(furan-2-yl)-4-allyl-5-thio-1,2,4-triazole-1-yl)-α-alanine through the diastereoselective addition of 4-allyi-3-thio-5-(furan-2-yl)-1,2,4-triazole to the electrophilic C=C bond of dehydroalanine in Ni(II) complex of Shiff’s base with chiral auxiliary (S)-2-N-(N’-2-chlorbenzylprolyl)aminobenzophenone was carried out. The target aminoacid with high optical purity (ee > 99%) was isolated after decomposition of the mixture of diastereomeric complexes.